Legal Protection of Crypto Art Copyright As a Digital Asset Intellectual Property (Lex Jurnalica, 2023)
At present the existence of the internet has disrupted various sectors of life in civilization which has changed human behavior and habits. One form of change that has occurred is the emergence of cryptocurrency and blockchain technology innovations in the digital economy industry, especially in the field of digital transactions. Both of these technologies were originally developed by digital artists to give birth to an invention in the form of crypto art which is given a Non-Fungible Token and has been encrypted via the blockchain and cannot be duplicated which shows the owner of the authenticity of someone's work. However, there are several NFT works that conflict with the concept of copyright law and violate copyright in the digital space. The research method used is normative juridical which is analyzed based on a qualitative approach. The focus of the research was carried out on secondary data in the form of library materials regarding intellectual property rights, digital copyrights, and virtual jurisdictions in their regulation and implementation in Indonesia. The result of this study is that NFT works have received legal protection through. However, Indonesian copyright law does not yet regulate the virtual jurisdictions, but in the Information and Electronic Transactions Acts it is possible to extend jurisdiction to the virtual world so that it reaches the imposition of laws on foreign marketplaces such as OpenSea and actors from other countries.Keywords: Copyright, Non-Fungible Token (NFT), Virtual Jurisdiction